2020
DOI: 10.1016/j.jmmm.2020.166855
|View full text |Cite
|
Sign up to set email alerts
|

Neutron inelastic scattering study of rare-earth orthoferrite HoFeO3

Abstract: By the single crystal inelastic neutron scattering the orthoferrite HoFeO3 was studied. We show that the spin dynamics of the Fe subsystem does not change through the spin-reorientation transitions. The observed spectrum of magnetic excitations was analyzed in the frames of linear spin-wave theory. Within this approach the antiferromagnetic exchange interactions of nearest neighbors and next nearest neighbors were obtained for Fe subsystem. Parameters of Dzyaloshinskii-Moriya interactions at Fe subsystem were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
4
16
0
Order By: Relevance
“…The critical field required for this first-order transition increases with decreasing temperature [23]. It is apt to compare these phases with those in the parent orthoferrites, HoFeO 3 and DyFeO 3 [19,20,22]. In HoFeO 3 , phase transitions occur in the following order as the temperature decreases: [18].…”
Section: Magnetic Phases and Spin Re-orientation In Ho05dy 05 Feo3mentioning
confidence: 99%
See 1 more Smart Citation
“…The critical field required for this first-order transition increases with decreasing temperature [23]. It is apt to compare these phases with those in the parent orthoferrites, HoFeO 3 and DyFeO 3 [19,20,22]. In HoFeO 3 , phase transitions occur in the following order as the temperature decreases: [18].…”
Section: Magnetic Phases and Spin Re-orientation In Ho05dy 05 Feo3mentioning
confidence: 99%
“…[19][20][21]. Alternatively, some neutron studies on single crystal HoFeO 3 claimed that there are two SRTs; Γ 4 55K − −− → Γ 1 36K − −− → Γ 2 [22]. Chakraborty et al [23] reported the presence of two-fold SRT, in their magnetic studies on single crystals of Ho 0.5 Dy 0.5 FeO 3 i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in order to obtain a proper description of spin waves one has to take into account exchange interactions within the second coordination sphere. Due to the structural distortion, the exchange interactions within each coordination sphere are slightly (∼10%) anisotropic with J c > J ab [60][61][62].…”
Section: Short Review Of Spin Dynamics In the Transition-metal Subsystemmentioning
confidence: 99%
“…Comprehensive investigations of the spin dynamics in the transition-metal subsystem were mainly focused on the Fe 3+ sublattice in orthoferrites [14,20,22,[59][60][61][62].…”
Section: Short Review Of Spin Dynamics In the Transition-metal Subsystemmentioning
confidence: 99%
“…Due to the structural distortion, the exchange interactions within each coordination sphere are slightly (∼ 10 %) anisotropic with J c > J ab [60][61][62].…”
Section: ]mentioning
confidence: 99%